(untitled) (Research, Society and Development, 2021)
The objective of this article is to report the experience of the FHS teams of a health unit, regarding the reorganization of the flow of care in order to improve access in times of pandemic due to the COVID-19. It consists of a descriptive study, which sought to reorganize the flow and care, aiming to provide full access to people in the health service, directly or indirectly, avoiding the number of contagion and infection by COVID-19 among the population, reducing the risk of contagion to the professionals of the unit, avoid the rapid spread of the virus. It is noticed that the process of organizing the flow of the unit had good results, such as interprofessional participation and patient compliance, the team was able to meet the basic needs of patients, maintaining links with users prioritizing chronic and decompensated situations, as well as preventive care. focusing on health promotion, emphasizing the prevention of infection by Sars-Cov 2.